Aleksander Wat i romantyzm. (Jeszcze) - Kuczera-Chachulska, Bernadetta (Colloquia Litteraria, 2012)
Aleksander Wat and romanticism (once more) In the sketch, the problem taken is the relation of Aleksander Wat to the Polish romanticism, both in terms of how to troubleshoot inherently more formal as well as final transfer of the works. Analysis of individual poems (including The Persian Parable, Across the Square) lead to the conclusion of a distinct connection between Wat and the Lausanne lyricism of Adam Mickiewicz.